2005
DOI: 10.1677/joe.1.06099
|View full text |Cite
|
Sign up to set email alerts
|

The estrogen receptor α Σ3 mRNA splicing variant is differentially regulated by estrogen and progesterone in the rat uterus

Abstract: The gene for estrogen receptor (ER ) has been shown to be under complex hormonal control and its activity can be regulated by mRNA alternative splicing. Here we examined the regulation of ER transcription and translation in the rat uterus by ovarian steroid hormones. We examined whether expression of ER mRNA splice isoforms is hormonally regulated in ovariectomized (OVX) and cycling rats. Adult OVX female rats were treated daily with 17-estradiol (E 2 ) (0·05 µg/rat or 5 µg/rat), progesterone (P 4 ) (1 mg/rat)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 35 publications
4
16
0
Order By: Relevance
“…2C). This structure is similar to that of the ΔE2,3 or ΔE3 variants detected in mammalian tissues (Pasqualini et al, 1999;Poola et al, 2000;Perlman et al, 2005;Varayoud et al, 2005), which lack both exons 2 and 3 or exon 3 only, and the in vitro translated human ERαΔE3 protein was unable to bind DNA or activate ERE-driven transcription but could bind E 2 , translocate to the nucleus and negatively affect wt-ERα transactivation activity at an ERE promoter (Bollig and Miksicek, 2000). In addition and like wt-ERα, the human ΔE3 protein could support transcriptional activation of promoters regulated by AP-1 and Sp-1 elements (Bollig and Miksicek, 2000;Koduri et al, 2006).…”
Section: Erα Exon2-deleted Transcript Variantssupporting
confidence: 68%
“…2C). This structure is similar to that of the ΔE2,3 or ΔE3 variants detected in mammalian tissues (Pasqualini et al, 1999;Poola et al, 2000;Perlman et al, 2005;Varayoud et al, 2005), which lack both exons 2 and 3 or exon 3 only, and the in vitro translated human ERαΔE3 protein was unable to bind DNA or activate ERE-driven transcription but could bind E 2 , translocate to the nucleus and negatively affect wt-ERα transactivation activity at an ERE promoter (Bollig and Miksicek, 2000). In addition and like wt-ERα, the human ΔE3 protein could support transcriptional activation of promoters regulated by AP-1 and Sp-1 elements (Bollig and Miksicek, 2000;Koduri et al, 2006).…”
Section: Erα Exon2-deleted Transcript Variantssupporting
confidence: 68%
“…Since sexual differentiation of the hypothalamus is estrogen-dependent and mediated at least partly through ERa (Simerly et al 1997), BPA deregulation of this receptor could affect the natural estrogen-directed dimorphisms of POA circuits. In a previous work performed in our laboratory, it has been demonstrated that low and high doses of estrogen can differentially regulate the splicing of the rat ERa mRNA coding region (Varayoud et al 2005). Selective promoter usage and alternative mRNA splicing events are estrogen-dependent mechanisms of ERa gene variation, arising as sources of complexity in the endocrine disruptor's toxicology.…”
Section: Discussionmentioning
confidence: 97%
“…A standard immunohistochemical technique (avidin-biotinperoxidase) was used to visualize ERa immunostaining intensity and distribution following a previously described protocol (Munoz de Toro et al 1998, Varayoud et al 2005. Overnight incubation at 4 8C was performed by applying a diluted mouse monoclonal antibody raised to full-length recombinant human ERa (working dilution 1:200; clone 6F-11, Novocastra, Newcastle upon Tyne, UK), followed by incubation with a biotinylated secondary antibody (working dilution 1:80; Sigma-Aldrich).…”
Section: Era Expression Detected By Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…In uterus, many ERα-splicing variants have been reported (Varayoud et al 2005), including the aforementioned truncated variants. Noticeably, only iAs was able to augment full-length ERα expression in both tissues, whereas Cd did not modify it.…”
Section: S a Ronchetti And Othersmentioning
confidence: 99%